Taking stock of ethics and compliance programs as anticorruption mechanisms: an integrative review - Chaves, Renato L. P. (Journal of business ethics, 2025)
Anticorruption regulators delegate to organizations part of the responsibility for deterring corruption in the form of ethics and compliance programs (ECPs), also referred to as compliance programs, ethics programs, and integrity programs. From this anticorruption perspective, organizations are expected to design and implement programs that comply with general criteria established by regulators to achieve a specific social goal - reducing corruption. This integrative review examines how different communities of practice analyze ECPs in their role as anticorruption mechanisms. Based on a conceptualization of ECP derived from theories of regulation, the review integrates the fragmented literature at the intersection of ECPs and corruption and uncovers connections across communities of practice to propose new insights and research directions. To achieve this objective, the review proposes a process-oriented anticorruption multi-level integrative framework that (1) situates ECPs in the anticorruption process that originated them and (2) identifies the areas where cross-fertilization of ideas from different communities of practice can contribute to redirecting future research. The review concludes with a research agenda that can help advance knowledge applicable to ECPs as anticorruption mechanisms and to other self-regulatory initiatives against grand societal challenges.